English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

well Dear;
f(x) = (5x+8) / (5x-2)

{
if f(x) = u(x) / v(x)
f'(x) = ( u'(x) (v(x) - v'(x) u(x) / [ v(x^2)]
}

{ if f(x) = m*x^n ; f'(x) = (m*n)*x^(n-1) }

if u(x) = (5x+8) ; u'(x) = 5
&
v(x) = (5x-2) ; v'(x) = 5
well dear just follow the formula;
f'(x) = ( u'(x) (v(x) - v'(x) u(x) / [ v(x^2)]
f'(x) = [(5*(5x-2)) - (5*(5x+8)) ] / [(5x-2)^2 ]
f'(x) = [(5*(5x-2) / (5x-2)^2] - [ (5*(5x+8)) / (5x-2)^2]
f'(x) =[ 5 / (5x-2)] - [5*(5x+8)) / (5x-2)^2]

Good Luck, It is your correct answer.

2006-09-23 06:27:05 · answer #1 · answered by sweetie 5 · 1 0

d/dx[ (5x+8)/(5x+2) ]
Let, 5x+2 = a, so 5x+8 = a+6
The differentiation reduces to d/da [ (a+6)/a ] * d/dx [a]
Now solve it.

2006-09-23 11:58:07 · answer #2 · answered by astrokid 4 · 0 1

f(x) = (5x + 8)/(5x - 2)

f'(x) = (((5x - 2)(5x + 8)') - ((5x - 2)'(5x + 8)))/((5x - 2)^2)
f'(x) = (((5x - 2)(5)) - (5(5x + 8)))/((5x - 2)(5x - 2))
f'(x) = (25x - 10 - 25x - 40)/(25x^2 - 10x - 10x + 4)
f'(x) = (-50)/(25x^2 - 20x + 4)

2006-09-23 14:16:19 · answer #3 · answered by Sherman81 6 · 0 1

-50/(5x-2)^2

2006-09-23 11:58:35 · answer #4 · answered by Greg G 5 · 0 1

-50/(5x-2)^2

2006-09-23 12:24:38 · answer #5 · answered by rwbblb46 4 · 0 1

fedest.com, questions and answers